Intraspecific variation in migration timing of green sturgeon in the Sacramento River system. Issue 6 (16th June 2022) - Colborne, Scott F.; Sheppard, Lawrence W.; O'Donnell, Daniel R.; Reuman, Daniel C.; Walter, Jonathan A.; Singer, Gabriel P.; Kelly, John T.; Thomas, Michael J.; Rypel, Andrew L.
Abstract: Understanding movement patterns of anadromous fishes is critical to conservation and management of declining wild populations and preservation of habitats. Yet, the duration of observations for individual animals can constrain accurate descriptions of movements. In this study, we synthesized over a decade (2006–2018) of acoustic telemetry tracking observations of green sturgeon ( Acipenser medirostris ) in the Sacramento River system to describe major anadromous movement patterns. We observed that green sturgeon exhibited a unimodal in‐migration during the spring months but had a bimodal distribution of out‐migration timing, split between an "early" out‐migration (32%) group during May–June, or, alternatively, holding in the river until a "late" out‐migration (68%), November–January. Focusing on these out‐migration groups, we found that river discharge, but not water temperature, may cue the timing of migration and that fish showed a tendency to maintain out‐migration timing between subsequent spawning migration events. We recommend that life history descriptions of green sturgeon in this region reflect the distinct out‐migration periods described here. Furthermore, we encourage the continued use of biotelemetry to describe migration timing and life history variation, in not only this population but also other green sturgeon populations and other species.